Spontaneous rupture of liver abscess with biliary communication presenting as a lumbar mass - Bhandarwar, Ajay; Tandur, Amarjeet; Kharmutee, Geoffrey; Rathod, Akshay; Dodke, Kaustubh; Rathod, Abhishek (International Surgery Journal, 2021)
Pyogenic liver abscess was first reported in the writings of Hippocrates, which was based on the type of fluid recovered from the abscess related to a high mortality rate ranging between 15% and 19% at that time. However in 1938, Ochsner and De Bakey described the recommended surgical treatment as the primary treatment modality. Surgery remained the therapy of choice until the mid-1980s, when percutaneous drainage was shown to be a safer alternative in many cases. Spontaneous rupture of liver abscess may occur free in the peritoneal cavity or in neighbouring organs, an event which is generally considered as a surgical emergency, while localized rupture can be managed with drainage, either percutaneous or surgical/minimal invasive techniques and addition of appropriate antibiotic treatment. In cases where there is uneventful rupture of abscess and localized to the neighbouring organs and tissues can be successfully treated by a combination of broad-spectrum antibiotics and percutaneous drainage and endoscopic management.